Visual timing and adaptive behavior in a road-crossing simulation study - te Velde, A. F.; van der Kamp, J.; Barela, J. A.; Savelsbergh, GJP (Elsevier B.V., 2005)
In this road-crossing simulation study, we assessed both participant's ability to visually judge whether or not they could cross a road, and their adaptive walking behavior. To this end, participants were presented with a road inside the laboratory on which a bike approached with different velocities from different distances. Eight children aged 5-7, ten children aged 10-12, and ten adults were asked both to verbally judge whether they could cross the road, and to actually walk across the road if possible. The results indicated that the verbal judgments were not similar to judgments to actually cross the road. With respect to safety and accuracy of judgments, groups did not differ from each other, although the youngest group tended to be more cautious. All groups appeared to use a strategy to cross the road based both on the distance and the velocity of the approaching bike. Young children waited longer on the curb before crossing the road than older children and adults. All groups adjusted their crossing time to the time-to-arrival of the bike. These findings are discussed in relation to the ecological psychological approach and the putative dissociation between vision for perception (i.e. verbal judgment) and vision for action (i.e. actual crossing). (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: visual timing; adaptive behavior; child pedestrians; safety